2017
DOI: 10.1136/emermed-2014-204306
|View full text |Cite
|
Sign up to set email alerts
|

Risk stratification of survival in injured patients with cardiopulmonary resuscitation within the first hour of arrival to trauma centre: retrospective analysis from the national trauma data bank

Abstract: Approximately 13% of patients who had CPR within an hour of arrival to a trauma centre survived their injury. Therefore, implementation of an aggressive first hour in-hospital resuscitation strategy may result in better survival outcomes for this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 17 publications
3
12
4
Order By: Relevance
“…This differs from previous studies 5,16,19 where no similar associations were reported. Patients in the younger age are usually expected to have better odds of survival because of lower comorbidities.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This differs from previous studies 5,16,19 where no similar associations were reported. Patients in the younger age are usually expected to have better odds of survival because of lower comorbidities.…”
Section: Discussioncontrasting
confidence: 99%
“…13,16 Young, white and male individuals continue to be mostly affected by traumatic arrests. 1,5,11 Improved survival in traumatic arrests presenting to U.S hospitals has been previously attributed to the increasing frequency of emergency interventions such as ED thoracotomy and other procedures. 17 Variation in survival rates of patients with traumatic arrest is however mostly related to differences in study sample selections with most studies including in the denominator arrests that are not transported to hospitals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study conducted throughout the 1980s to the 1990s, the ERC reported that cardiac arrest trauma patients had a survival rate below 2%. However, according to a German and American study conducted using cardiac arrest trauma patients from the DGU registry, the survival rate of such patients was 17.2% and 13% respec-tively, a higher rate than was previously thought [55,56]. It must be noted, though, that the American study only included cardiac arrest patients who arrived within the ICU bay within 1 hour.…”
Section: Evidence Summarymentioning
confidence: 97%